Echocardiographic predictors of long‐term adverse cardiovascular outcomes in participants with and without diabetes mellitus: A follow‐up analysis of the Copenhagen City Heart Study. Issue 10 (12th July 2021) - Özbek, Burcu Tas; Modin, Daniel; Møgelvang, Rasmus; Jørgensen, Peter Godsk; Jensen, Magnus Thorsten; Schnohr, Peter; Gislason, Gunnar Hilmar; Biering‐Sørensen, Tor
Abstract: Background: Previous studies have identified several echocardiographic markers of cardiac dysfunction in participants with diabetes mellitus, including E/e'. However, previous studies have been limited by short follow‐up duration or low statistical power, and none have assessed whether echocardiographic predictors of adverse cardiovascular outcome differ between individuals with DM and individuals without DM. Methods: A total of 1997 individuals from the general population without heart disease had an echocardiogram performed in 2001 to 2003. Diabetes was defined as HbA1c ≥6.5% (≥48 mmol/mol), non‐fasted blood glucose ≥11.1 mmol/L or the use of glucose lowering medication. The end‐point was a composite of heart failure (HF), ischemic heart disease (IHD) and cardiovascular death (CVD). Results: At baseline, a total of 292 participants (15%) had diabetes. Median follow‐up time was 12.4 years (interquartile‐range: 9.8–12.8 years) and follow‐up was 100%. During follow‐up, 101 participants (35%) with diabetes and 281 participants without diabetes (16%) reached the composite end‐point. The prognostic value of E/e' was significantly modified by diabetes (p for interaction: 0.003). In participants with diabetes, only E/e' remained an independent predictor of outcome in a final multivariable model adjusted for clinical and echocardiographic parameters (HR 1.08, 95% CI 1.00–1.17, p = 0.0041, per 1 increase). In participants without diabetes, left ventricular mass index (LVMI), left ventricular ejection fraction (LVEF) and a' remained independent predictors of outcome when adjusted for clinical and echocardiographic parameters. In individuals with diabetes, only E/e' added incremental prognostic value to risk factors from the SCORE risk chart and the ACC/AHA Pooled Cohort Equation. Conclusion: In individuals with diabetes from the general population, E/e' is a stronger predictor of cardiovascular mortality and morbidity than in individuals without diabetes and contributes with incremental prognostic value in addition to established cardiovascular risk factors.